2014
DOI: 10.1177/0004865814545684
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of satisfaction with the police in the United States and Australia

Abstract: This study comparatively examines three major models of citizens' satisfaction with the police, using two similar community surveys on policing from Cincinnati, Ohio, USA and Queensland, Australia. It tests the wider applicability of the demographic model, the neighborhood condition model, and the prior contacts with police model and analyzes whether the effects of common determinants on citizens' satisfaction remain the same across the two international samples. Results from a series of comparisons show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 63 publications
6
29
0
Order By: Relevance
“…Although perp walks have a long history in American criminal justice, we have been unable to find any empirical studies aimed at examining public opinion on perp walks. This absence stands in stark contrast to the number of studies on public opinion aimed at examining the integrity of the police (e.g., Dai and Jiang, 2016;Gabbidon and Higgins, 2009;Garcia and Cao, 2005;Hagan and Albonetti, 1982;Hagan et al, 2005). Nevertheless, extrapolating from research on confidence in the police, it seems reasonable to speculate that individuals who have a low opinion of the police will be less likely to support the use of perp walks because of the possibility that unjustly accused suspects will be unnecessarily publicly shamed and punished by this practice.…”
Section: Confidence In the Police And The Importance Of Due Processmentioning
confidence: 85%
See 1 more Smart Citation
“…Although perp walks have a long history in American criminal justice, we have been unable to find any empirical studies aimed at examining public opinion on perp walks. This absence stands in stark contrast to the number of studies on public opinion aimed at examining the integrity of the police (e.g., Dai and Jiang, 2016;Gabbidon and Higgins, 2009;Garcia and Cao, 2005;Hagan and Albonetti, 1982;Hagan et al, 2005). Nevertheless, extrapolating from research on confidence in the police, it seems reasonable to speculate that individuals who have a low opinion of the police will be less likely to support the use of perp walks because of the possibility that unjustly accused suspects will be unnecessarily publicly shamed and punished by this practice.…”
Section: Confidence In the Police And The Importance Of Due Processmentioning
confidence: 85%
“…Attitudes toward the police can even be influenced vicariously, as research findings have shown that hearing about the bad experiences that others have had with the police is associated with negative attitudes toward the police (Hurst, Frank, and Browning, 2000;Rosenbaum, Schuck, Costello, Hawkins, and Ring, 2005). After controlling for unsatisfactory prior contacts, however, a recent comparative study of satisfaction with the police in the United States and Australia found no race differences in general satisfaction with the police (Dai and Jiang, 2016). In short, the fundamentally different experience that people of color historically have had with the criminal justice system clearly is an important consideration in the formation of their generally skeptical attitudes toward punitive criminal justice practices.…”
Section: Race and Ethnicitymentioning
confidence: 99%
“…Factors affecting satisfaction with police include demographics, contact with the police and neighborhood context variables. Considering that the proportion of local residents who have contact with the police is not high (Wu et al , 2009), satisfaction with police can be influenced by the characteristics of the local community (Hawdon and Ryan, 2003; Dai and Jiang, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This claim is supported by many studies showing that crime rates are negatively associated with satisfaction with the police (Kelly and Swindell, 2002; Lai and Zhao, 2018; Reisig and Parks, 2000; Wu et al , 2009). In terms of disorder, a number of studies have shown that satisfaction with police was significantly lower in disordered areas (Dai and Jiang, 2016; Lai and Zhao, 2018; Reisig and Parks, 2000; Sprott and Doob, 2009). In sum, residents feel that the police are responsible for the safety and quality of life in the community (Reisig and Parks, 2000), and satisfaction with the police may decrease if the police are unsuccessful in controlling crime and disorder (Bridenball and Jesilow, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Brown and Benedict, 2002; Dai and Johnson, 2009; Cao, 2015). As Dai and Jiang (2016) surmise, healthy relations between the public and the police promote public cooperation with the police and enhance police legitimacy and trustworthiness. Further, positive public attitudes toward the police may be instrumental in reducing crime (Tyler, 2004).…”
Section: Introductionmentioning
confidence: 99%